2002
DOI: 10.1590/s0365-05962002000500012
|View full text |Cite
|
Sign up to set email alerts
|

Pitiríase Versicolor

Abstract: Resumo: A expressão pitiríase versicolor define uma infecção fúngica superficial caracterizada por alterações na pigmentação cutânea. O distúrbio de pigmentação é devido à colonização do estrato córneo por um fungo dimórfico, lipofílico, encontrado na flora normal da pele, conhecido como Malassezia furfur. Trata-se de doença prevalente nos trópicos, mas também comum em climas temperados. Há vários tratamentos disponíveis com taxas elevadas de cura, porém as recorrências são freqüentes. Palavras-chave: Fungos; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
(31 reference statements)
1
9
1
1
Order By: Relevance
“…There is slight collapse of the keratin in this region, which facilitates observing fine desquamation. 5,20 …”
Section: Introductionmentioning
confidence: 99%
“…There is slight collapse of the keratin in this region, which facilitates observing fine desquamation. 5,20 …”
Section: Introductionmentioning
confidence: 99%
“…the palms and soles of the feet) (Peyrefitte, 1997;SFD, 2005). The face is the most common location reported in most studies (Miskeen and Shroff 1984;Faergemann 1999;De Oliveira and Steiner 2002;Jena et al, 2005;Silva-Rocha et al, 2017), though the neck and trunk were the common locations reported in Burkina Faso (Zida et al, 2015). In this study, the back was the most common location of mycosis, followed by the chest.…”
Section: Discussionmentioning
confidence: 99%
“…On the face, lesions are more common in children than in adults. 1,18 The following frequencies of lesions were observed through a study performed in Manaus (Brazil): widespread (31.50%), trunk (20.65%), upper limbs (13.75%), lower limbs (9.50%), face (8.85%). 19 …”
Section: Discussionmentioning
confidence: 99%
“…It is a pigmentation disorder clinically characterized by the presence of macular lesions, initially perifollicular with fine scaling, variable color spanning from white to brown and occasionally becoming erythematous. 1-3 …”
Section: Introductionmentioning
confidence: 99%